Clinical Characteristics and Outcomes of Children With Extracorporeal Membrane Oxygenation in a Developing Country: An 11-Year Single-Center Experience - Wirapatra Iamwat (2022)
Introduction: Extracorporeal Membrane Oxygenation (ECMO) is a lifesaving procedure for patients with refractory cardiac or respiratory failure. The indications for ECMO are growing, and it is increasingly being used to support cardiopulmonary failure in children. However, the risks and benefits of ECMO should be weighed before deploying it on the patients. The objectives of this study were to identify the mortality risk factors and to determine the ECMO outcomes. Methods: The retrospective chart reviews were done for all patients aged 1 day−20 years old receiving ECMO between January 2010 and December 2020. Results: Seventy patients were enrolled in the study. The median age was 31.3 months. The incidence of VA and VV ECMO was 85.7 and 14.3%, respectively. The most common indication for ECMO was the failure to wean off cardiopulmonary bypass after cardiac surgery. Pre-existing acute kidney injury (OR 4.23; 95% CI 1.34–13.32, p = 0.014) and delayed enteral feeding (OR 3.85, 95% CI 1.23–12.02, p = 0.020), and coagulopathy (OD 12.64; 95% CI 1.13–141.13, p = 0.039) were associated with the higher rate of mortality. The rates of ECMO survival and survival to discharge were 70 and 50%, respectively. Conclusion: ECMO is the lifesaving tool for critically ill pediatric patients. Pre-existing acute kidney injury, delayed enteral feeding, and coagulopathy were the potential risk factors associated with poor outcomes in children receiving ECMO. However, ECMO setup can be done successfully in a developing country.